Հորթերի կորոնավիրուսով և էնտերոբակտերիաներով վարակվածության ուսումնասիրությունն Արագածոտնի մարզում - Գէօհյուլեան, Վ. Ս.; Սարգսյան, Մ. Ա. (ՀԱԱՀ հիմնադրամ)
Հետազոտությունների համաձայն՝ նորածին հորթերի կորոնավիրուսային հիվանդության հիմնական պատճառը մայրերի վարակակրությունը, ցուրտ և խոնավ պայմաններն են: Հիվանդությունն ախտորոշվել է ըստ հեմագլյուտինացման ռեակցիայի, Bovine Enterichek թեստի և մանրէաբանական եղանակների: Հիվանդացության, մահացականության գործակիցները համապատասխանաբար կազմել են 0,1 (10 %), 0,6 (60 %), տնտեսական վնասը՝ 209400 դրամ: Հիմք ընդունելով «БольшеВАК» պատվաստանյութի արդյունավետությունը՝ առաջարկում ենք անապահով տնտեսություններում իրականացնել կանխարգելիչ պատվաստումներ: Согласно исследованиям, основными причинами заболевания коронавирусом новорожденных телят являются инфицированные матери, холодные и сырые условия. Заболевание было диагностировано посредством реакции гемагглютинации, теста Bovine Enterichek и микробиологических методов. Коэффициенты заболеваемости и смертности составили соответственно 0.1 (10 %) и 0.6 (60 %), а экономический ущерб – 209 400 драмов. Основываясь на эффективности вакцины “БольшеВАК”, предлагаем в неблагополучных хозяйствах проводить профилактические прививки. Calf coronavirus (viral diarrhea) is an endemic disease that is mainly spread by maternal infectivity, cold, wet conditions and crowded housing conditions. Feces were sampled from the rectum of 50 newborn, 3-35-day-old calves. The samples were examined by microbiological, hemagglutination and Bovine enterichek accelerated test (antibody strips) in the ANAU Research Center of Veterinary Medicine and Veterinary Sanitary Examination. Epidemiological data, manifestations of clinical symptoms, patho-anatomical changes, hemagglutination reaction and Bovine enterichek test were used to identify the infection of 3-35-day-old calves. Feces with mucus content from the rectum of calves with diarrhea (50 samples), internal organs (spleen, liver, etc.) and affected small intestines of fallen 3-7-day-old animals (3 heads) were examined. During epidemiological studies, an increase in body temperature (42 0C), anorexia, exhaustion, depression and watery- slimy diarrhea were observed in sick calves. Clots were found on the walls of the arteries of dead animals, inflammation and hemorrages were found in the lymph nods and kidneys. According to epidemiological, clinical symptoms, patho-anatomical changes, microbiological research, as well as hemagglutination reaction and Bovine enterichek rapid test data, both coronavirus and enterobacterial diseases were detected in animals at the same time. As a result, farmers and villagers suffered economic losses due to newborn calf falls. The disease was diagnosed according to hemagglutination reaction, Bovine enterichek test and microbiological methods. Morbidity and mortality rates were respectively 0.1 (10 %), 0.6 (60 %), economic loss – AMD 209 400. Based on the effectiveness of the “BolsheVac” (“БольшеВАК”) vaccine, we propose to carry out preventive vaccinations in vulnerable farms.
Keywords: Անասնաբուժական բժշկագիտություն և անասնաբուծություն